2019
DOI: 10.1002/rcm.8398
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of quantifying sodium channel Nav1.6 protein in mouse brain using targeted ultra‐high‐performance/electrospray ionization multiple reaction monitoring mass spectrometry

Abstract: Rationale Nav1.6 is a transmembrane voltage gated sodium channel implicated in various forms of epilepsy. Modulation of its activity in epilepsy animal models can be accomplished using inhibitors which may result in changes in its expression. There is a need to generate reliable quantitative measurements of Nav1.6 expression in animal models. This research explores the feasibility of quantifying Nav1.6 expression in mouse brains using targeted multiple reaction monitoring (MRM) mass spectrometry. Methods A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, time courses following the signals of the Na v selected peptides in the presence of Λ‐phosphatase added after the proteolysis of solubilized mouse, rat, and human brain membrane proteins were carried out. In a previous publication, 12 we demonstrated that the peptide DSLFIPIR, used in the quantification of Na v 1.6, did not show signs of phosphorylation. Figure 3A shows the time course of the dephosphorylation experiment using a phosphorylated peptide GAQA S PPPIAPYP S PTR in the presence of Λ‐phosphatase as positive control, where the underscored and bold serine residues indicate the location of phosphorylation, while the same dephosphorylation treatment was done for the selected Na v 1.1, 1.2, and 1.6 peptides in the mouse, rat, and human brain membrane protein samples, is shown in Figure 3B.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Therefore, time courses following the signals of the Na v selected peptides in the presence of Λ‐phosphatase added after the proteolysis of solubilized mouse, rat, and human brain membrane proteins were carried out. In a previous publication, 12 we demonstrated that the peptide DSLFIPIR, used in the quantification of Na v 1.6, did not show signs of phosphorylation. Figure 3A shows the time course of the dephosphorylation experiment using a phosphorylated peptide GAQA S PPPIAPYP S PTR in the presence of Λ‐phosphatase as positive control, where the underscored and bold serine residues indicate the location of phosphorylation, while the same dephosphorylation treatment was done for the selected Na v 1.1, 1.2, and 1.6 peptides in the mouse, rat, and human brain membrane protein samples, is shown in Figure 3B.…”
Section: Resultsmentioning
confidence: 64%
“…30,31 The mean number of Na v channels in the membrane can be estimated by dividing the mean current per cell by the single channel conductance. We have previously shown that the proposed targeted MRM method differentiates between the Na v 1.6 expression in Scn8a +/À mutant mouse hippocampal tissues (0.2 fmol/μg membrane protein) and their corresponding wild type (0.4 fmol/μg membrane protein), 12 as expected due to the introduced mutation. Similarly, the MRM method was applied to Scn1a +/À mutant mouse hippocampal tissues, which are expected to show about 50% Na v 1.1 expression of the wild type.…”
Section: Proteinmentioning
confidence: 67%
See 3 more Smart Citations